Comparative Evaluation Of Pattern Of Caries In Primary Maxillary First Molars And Mandibular First Molars In Children - S, UMAYAL.; EMG, SUBRAMANIAN; AS, SMILINE GIRIJA (The journal of contemporary issues in business and government, 2021)
The aim of this study is to assess the pattern of caries in primary maxillary and mandibular first molar in children visiting a University Dental Hospital.Dental caries is a significant oral health problem in children which compromises the overall well being of the child. The pattern of caries distribution in the deciduous teeth is not symmetrical with some teeth being more prone to decay as compared to others. In this present study, the various patterns of Dental Caries in primary maxillary and mandibular first molars will be assessed and comparative evaluation is done.A Sample of 566 patients visiting the hospital were taken (The University Dental Hospital). The Data is collected from Dental Information Archiving Software. All the case sheets were reviewed and clinical findings are recorded. The data is then tabulated and analysed with the help of SPSS and Excel.In this study it is observed that the patients with the caries on maxillary molars (63.4%) are more affected with caries then the people affected with caries on the mandibular molars (36.6%). It is also observed that the people with class 2 caries in the first molars. Class 1 caries (22.6%) were predominant than class 2 caries (13.6%). To one more observation , there was only (0.35%) for people affected with class 5 caries in mandibular molar . Whereas in maxillary molars , none of the people were affected with class 5 caries. Within the limits of the study , it is concluded that the patients with caries on maxillary first molars are more affected than the people affected with caries on mandibular first molars.